LOAD EQUIVALENCE TEST METHOD FOR FATIGUE LIFE OF MULTI-SITE-DAMAGE LARGE SIZE STRUCTURE PART - TIAN HongLei; SUN WeiGuang; YANG WenChao; XIE LiYang (Jixie qiangdu)
Owing to the dispersion of material and structure property,the fatigue life of a structure part depends on all its high stress sites. A multi-site damage structure is a series system with many weak links（ damage sites） in probability sense.Therefore,the fatigue life（ a random variable） of a complex structure part with multiple damage sites will be less than the life of the weakest site on the part. Owing to test equipment and conditions,the loads and stress state of a test part cannot exactly reproduce the real structure part in service. The present paper analyzed fatigue life influence factors for a large-size structure part test,expressed the relationship between fatigue life and number of high stress sites,studied fatigue life equivalence method when changing the fully reversed cyclic load in service into pulsation cyclic load in test. Through damage site number based load level adjustment and mean stress modification,this paper provides a load equivalence method to simplify fatigue test of large size multisite-damage parts. The results indicate that through such load transformation,the loading frequency of the electric-hydraulic servo test system can be increase from 2 Hz to 4 Hz,while the fatigue life distribution of the tested part keeps nearly the same as that of the service part.